Tensile Behavior of Geometrically Irregular Bagasse Fiber - Md Shahnewaz Bhuiyan; Muhommad Azizur Rahman; Md Shahriar Farabi; Md Mahedi Hasan (Applied Mechanics, 2021)
In the present work, an investigation on the surface topography and geometry variation of bagasse fibers was correlated with their mechanical properties via image analysis. The fibers were tested under a universal tensile testing machine and the diameter of the fibers was calculated using images obtained in a digital microscope. Furthermore, surface characterization and quantification were also performed using images obtained via SEM. The results showed that the surface roughness of alkali-treated bagasse fiber increased compared to that of the untreated one. Moreover, it was observed that the diameter variation of bagasse fiber along its length and among different fibers is not only variable but also unpredictable. The tensile test results revealed that bagasse fibers showed lower stress at a rupture with considerable scatter. It can be inferred that the synergistic effect of thick bagasse fiber, bagasse fiber diameter variations along its length and among fibers, and the fiber fracture mechanism establishes a local condition for fracture and resulted in such variations in tensile properties. Finally, the results clearly showed that the two-parameter Weibull fit the experimental data fairly well (<semantics>R2=0.97</semantics>). The Weibull modulus <semantics>(m)</semantics> was found to be 1.7, indicating that the strength distribution is high.